Evaluation of fly ash pellets for phosphorus removal in a laboratory scale denitrifying bioreactor. (1st February 2018) - Li, Shiyang; Cooke, Richard A.; Huang, Xiangfeng; Christianson, Laura; Bhattarai, Rabin
Abstract: Nitrate and orthophosphate from agricultural activities contribute significantly to nutrient loading in surface water bodies around the world. This study evaluated the efficacy of woodchips and fly ash pellets in tandem to remove nitrate and orthophosphate from simulated agricultural runoff in flow-through tests. The fly ash pellets had previously been developed specifically for orthophosphate removal for this type of application, and the sorption bench testing showed a good promise for flow-through testing. The lab-scale horizontal-flow bioreactor used in this study consisted of an upstream column filled with woodchips followed by a downstream column filled with fly ash pellets (3 and 1 m lengths, respectively; both 0.15 m diameter). Using influent concentrations of 12 mg/L nitrate and 5 mg/L orthophosphate, the woodchip bioreactor section was able to remove 49–85% of the nitrate concentration at three hydraulic retention times ranging from 0.67 to 4.0 h. The nitrate removal rate for woodchips ranged from 40 to 49 g N/m 3 /d. Higher hydraulic retention times (i.e., smaller flow rates) corresponded with greater nitrate load reduction. The fly ash pellets showed relatively stable removal efficiency of 68–75% across all retention times. Total orthophosphate adsorption by the pellets was 0.059–0.114 mg P/g which was far less than the saturated capacity (1.69 mg/g; based on previous work). The fly ash pellets also removed some nitrate and the woodchips also removed some orthophosphate, but these reductions were not significant. Overall, woodchip denitrification followed by fly ash pellet P-sorption can be an effective treatment technology for nitrate and phosphate removal in subsurface drainage. Highlights: Orthophosphate removal efficiency of fly ash pellet was investigated. Fly ash pellet also contributed to nitrate removal in this system. The orthophosphate removal rate was constant under different flow rate.